Enhancing National Security: Strategic Policy Development in Defense Management - Sarjito, Aris (Jurnal Pelita Nusantara, 2024)
This research explores the complexities of enhancing national security through strategic policy development in defense management, focusing on the influences of technological advancements, geopolitical shifts, and strategies for addressing non-traditional security threats. The background underscores the evolving landscape of global security challenges, necessitating innovative approaches beyond conventional military strategies. This study examines how technological advances such as artificial intelligence, machine learning, and cybersecurity measures shape defense management strategies. It also aims to understand the impact of geopolitical shifts on national defense policies, emphasizing the need for adaptable and forward-thinking strategies. Additionally, the research investigates effective measures for addressing non-traditional security threats, including economic, environmental, and health security considerations. Qualitative research methods using secondary data include literature review and case study analysis. Findings reveal that technological innovations enhance threat detection, decision-making processes, and defense capabilities. Geopolitical shifts necessitate continuously reassessing defense priorities, influencing strategy formulation and international alliances. Effective strategies for non-traditional threats emphasize integrated approaches across economic, environmental, and health domains. In conclusion, a comprehensive and adaptive defense policy framework is essential for mitigating multifaceted security challenges and ensuring national resilience.